2017
DOI: 10.32607/20758251-2017-9-1-15-25
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics for the Investigation of Mycobacteria

Abstract: The physiology of Mycobacterium tuberculosis, the causative agent of tuberculosis, is being studied with intensity. However, despite the genomic and transcriptomic data available today, the pathogenic potential of these bacteria remains poorly understood. Therefore, proteomic approaches seem relevant in studying mycobacteria. This review covers the main stages in the proteomic analysis methods used to study mycobacteria. The main achievements in the area of M. tuberculosis proteomics are described in general. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 117 publications
0
5
0
Order By: Relevance
“…Due to limitations in the sensitivity of methods and in the complexity of analysis, proteomics is yet to reach the multifaceted scope of genomics and transcriptomics approaches [78]. However, the variation between protein abundance and corresponding mRNA abundance, suggests that proteomics provides a distinct and useful understanding of M.tb physiological responses and target expression [79].…”
Section: Target Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to limitations in the sensitivity of methods and in the complexity of analysis, proteomics is yet to reach the multifaceted scope of genomics and transcriptomics approaches [78]. However, the variation between protein abundance and corresponding mRNA abundance, suggests that proteomics provides a distinct and useful understanding of M.tb physiological responses and target expression [79].…”
Section: Target Identificationmentioning
confidence: 99%
“…A number of studies have revealed insights into the expression of M.tb proteins intracellularly and in vivo, confirming the expression of potentially druggable targets. There are broadly two proteomics strategies, firstly, a top-down approach whereby intact proteins are isolated from a biological sample and sorted by gel electrophoresis, based on their physical and chemical properties, before identification by mass spectrometry (MS) [78]. Popular in early proteomic research, this technique typically found 100 mycobacterial proteins, accounting for approximately 3% of the total M.tb proteome.…”
Section: Target Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Even then, proteomics has already enabled us to know some aspects of virulence and its mechanisms of action in Mtb strains. The next step for proteomics contribution in mycobacteria research, the analysis of the immune response of the host, is one of the ways to establish new treatment programs, especially in the current scenario of drug resistance [17].…”
Section: Proteomicsmentioning
confidence: 99%
“…In addition, particular attention has been directed toward emerging cases of drug-resistant M. tuberculosis strains, which are arising due to the mismanagement of anti-TB treatments that amplify clinical strains with genetic mutations, especially in the promoter region ( 2 ). Molecular assays based on mass spectrometry analysis are recognized as emerging tools for rapid mycobacterial identification and drug susceptibility assessments ( 3 5 ). High-end techniques such as matrix-assisted laser desorption ionization–time of flight mass spectrometry (MALDI-TOF MS) and liquid chromatography-tandem MS (LC-MS/MS) have been applied for M. tuberculosis identification and proteomics profiling.…”
Section: Introductionmentioning
confidence: 99%